2017
DOI: 10.1002/ejic.201700494
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Adducts of Phenyldioxophosphorane and Its Heavier Sulfur and Selenium Analogues

Abstract: The reactions of the N-heterocyclic carbene-phenylphosphinidene adducts (NHC)PPh with dioxygen, elemental sulfur or selenium are reported. For NHC = 1,3,4,5-tetramethylimidazolin-2-ylidene (IMe), the corresponding complexes (IMe)PE 2 Ph of phenyldioxophosphorane (PhPO 2 ), phenyldithioxophosphorane (PhPS 2 ) and phenyldiselenoxophosphorane (PhPSe 2 ) were isolated and fully characterised, including determination of their molecular structures by single-crystal X-ray diffraction analyses. For the adducts of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…Namely, upon exposure of NHC–phosphinidene adduct ( 2 ‐H) · PCHN( i Pr) 2 ( δ 31 P = –64.8) in benzene to air for several weeks a small amount of bis(oxide) 31 ( δ 31 P = 90.5) was obtained and crystallographically characterized (Scheme ) . Recently, the group of Tamm has demonstrated that 2· PPh, 5· PPh and 6· PPh can also form the corresponding bis(oxides) in the reaction with dioxygen, whereas the heavier sulfur and selenium analogues are selectively obtained only in the reaction of the sterically accessible 2· PPh with elemental sulfur or selenium, respectively …”
Section: Reactivity Of N‐heterocyclic Carbene–phosphinidene Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, upon exposure of NHC–phosphinidene adduct ( 2 ‐H) · PCHN( i Pr) 2 ( δ 31 P = –64.8) in benzene to air for several weeks a small amount of bis(oxide) 31 ( δ 31 P = 90.5) was obtained and crystallographically characterized (Scheme ) . Recently, the group of Tamm has demonstrated that 2· PPh, 5· PPh and 6· PPh can also form the corresponding bis(oxides) in the reaction with dioxygen, whereas the heavier sulfur and selenium analogues are selectively obtained only in the reaction of the sterically accessible 2· PPh with elemental sulfur or selenium, respectively …”
Section: Reactivity Of N‐heterocyclic Carbene–phosphinidene Adductsmentioning
confidence: 99%
“…5·PPh and 6·PPh can also form the corresponding bis(oxides) in the reaction with dioxygen, whereas the heavier sulfur and selenium analogues are selectively obtained only in the reaction of the sterically accessible 2·PPh with elemental sulfur or selenium, respectively. [45] Scheme 32. Reactions of (2-H)·PCHN(iPr) 2 with BH 3 and air.…”
Section: Oxidationmentioning
confidence: 99%
“…[15] Thermal fragmentation of 2(o-biphenylyl)-1,3,2-dioxaphospholane generates a monomeric metaphosphonate as evidenced by an intramolecular trapping reaction with the adjacent phenyl group to give 5-hydroxydibenzophosphole 5-oxide. [8,18] It has been shown that pyridine can be utilized as a ligand for the stabilization of sulfenes. [8,18] It has been shown that pyridine can be utilized as a ligand for the stabilization of sulfenes.…”
Section: Introductionmentioning
confidence: 99%
“…Tamm and co‐workers reported the insertion reaction of 9 into dioxygen giving the phosphinate compound 19 featuring a PO 2 − moiety (Scheme ) . The 31 P NMR spectrum of 19 reveals the expected downfield shifted resonance at δ (P)=0.3 ppm (compare 9 : δ (P)=−18.9 ppm), being in the range for phosphane oxides .…”
Section: Imidazoliumyl‐substituted Phosphorus Compoundsmentioning
confidence: 98%
“…However, the reaction of 9 with elemental sulfur or selenium results in the C2−P bond cleavage under concomitant formation of the corresponding imidazole‐2‐thione or imidazole‐2‐selenone and PhPS 2 or PhPSe 2 , respectively. By using phosphanide compound 17 , featuring a sterically less demanding imidazoliumyl substituent, a successful insertion into elemental sulfur or gray selenium was achieved, giving compounds 20 and 21 , respectively (Scheme ) …”
Section: Imidazoliumyl‐substituted Phosphorus Compoundsmentioning
confidence: 99%